Dynamic Relationship between Government Spending and Private Consumption: Evidence from Cote d'Ivoire - Keho, Yaya (International Journal of Economics and Financial Issues, 2019)
This study tests the dynamic relationship between government and household consumption in Cote d'Ivoire. The ARDL bounds test and Johansen approach are employed to annual data covering the period 1970 to 2016. The results reveal a long run relationship between household consumption, real GDP and government consumption. In the long run, private consumption and per capita income have positive effects on government consumption. However, in the short run there is no causal relationship between the variables. Keywords: Government spending; private consumption; GDP. JEL Classifications: C22, E21, E62, H31 DOI: https://doi.org/10.32479/ijefi.7433